Disharmoni Peraturan Perundang-Undangan di Bidang Agraria (Lex Jurnalica, 2013)
AbstractDisharmony (disharmony) legislation also occur because of selfishness sectoral ministries/ agencies in the planning process and the legal establishment. In the harmonization of legislation is done at the central level , according to data from the Ministry of Justice and Human Rights in 2007, has made 25 of 27 harmonized draft laws proposed (92.59 %), 92 of the 107 draft regulations proposed (85.98 %); 7 of 9 proposed draft presidential regulation (77.77 %) . In the year 2008 has been harmonized 13 draft laws , draft regulations 64 and 6 draft presidential regulation. Setting the right to land is still causing a lot of problems with respect to sectoral activities , departmental and local (regional) . In his judgment , this is the result of a mismatch between the Agraria Law arrangements with other laws , such as: minning, Forestry, Spatial Planning and Investment, as well as among the Act, for example, Forestry and Mines . Based on the description of the background above, which is the case in this study were (1) legislation collide whatever sector (disharmony) with Agraria Law and (2) What are the benchmarks for assessment disharmony? The main objective of this research is to study the impact of the implementation of various laws and regulations relating to land and give you the option to harmonize , so that the legal framework for land management in Indonesia is compatible with the constitutional mandate . Based on the above background , the formulation of the problem and research objectives as well as objects of research about